Intricate Genetic Programs Controlling Dormancy in Mycobacterium tuberculosis - Eliza J.R. Peterson; Abrar A. Abidi; Mario L. Arrieta-Ortiz; Boris Aguilar; James T. Yurkovich; Amardeep Kaur; Min Pan; Vivek Srinivas; Ilya Shmulevich; Nitin S. Baliga (Cell Reports, 2020)
Summary: Mycobacterium tuberculosis (MTB) displays the remarkable ability to transition in and out of dormancy, a hallmark of the pathogen’s capacity to evade the immune system and exploit susceptible individuals. Uncovering the gene regulatory programs that underlie the phenotypic shifts in MTB during disease latency and reactivation has posed a challenge. We develop an experimental system to precisely control dissolved oxygen levels in MTB cultures in order to capture the transcriptional events that unfold as MTB transitions into and out of hypoxia-induced dormancy. Using a comprehensive genome-wide transcription factor binding map and insights from network topology analysis, we identify regulatory circuits that deterministically drive sequential transitions across six transcriptionally and functionally distinct states encompassing more than three-fifths of the MTB genome. The architecture of the genetic programs explains the transcriptional dynamics underlying synchronous entry of cells into a dormant state that is primed to infect the host upon encountering favorable conditions. : Mycobacterium tuberculosis (MTB) persists within the host by counteracting disparate stressors including hypoxia. Peterson et al. report a transcriptional program that coordinates sequential state transitions to drive MTB in and out of hypoxia-induced dormancy. Among varied properties, this program encodes advanced preparedness to infect the host in favorable conditions. Keywords: Mycobacterium tuberculosis, hypoxia, granuloma, dormancy, gene regulatory network, regulatory motifs, transcriptional state, reactor, systems biology, state transition